The spatial organization of pottery production in Huancito, Michoacan, Mexico - Eduardo Williams (Papers from the Institute of Archaeology, 1995)
This paper contributes to the study of the organization of space in pottery-producing households from the ethnoarchaeological perspective. The ethnoarchaeological approach is based on observation of contemporary cultural patterns to provide data and inferences to help in the interpretation of the archaeological record.
Keywords: household; ceramics; pottery; space